(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study is to determine the influence of conventional training methods and varied training methods on the forehand spin stroke skills of table tennis athletes at PTM Orbit Jaya Makassar. This research employed a quantitative method with an experimental design involving two groups of athletes. Each group consisted of seven male participants, with one group receiving conventional training and the other receiving varied training. Pre-test and post-test assessments were conducted to measure the athletes’ skill improvement. Data were analyzed using descriptive statistics and inferential analysis, including normality testing, homogeneity testing, and t-tests. The results showed that both training methods significantly improved the athletes’ forehand spin stroke skills. However, the group receiving varied training achieved a higher average post-test score compared to the group trained with the conventional method. These findings suggest that while both methods are effective, varied training contributes more substantially to improving athletes’ performance. It can be concluded that the implementation of both conventional and varied training methods has a significant positive impact on the forehand spin stroke skills of table tennis athletes at PTM Orbit Jaya Makassar.